Central Nervous System Involvement by Small Lymphocytic Lymphoma after a Myxoma-Related Embolic Event - Nicolas Gallastegui; Daniel P. Cassidy; Deborah O. Heros; Francisco Vega; Jonathan H. Schatz (Case Reports in Hematology)
Involvement of the central nervous system by chronic lymphocytic leukemia/small lymphocytic lymphoma is exceedingly rare, and currently no risk factors have been described. We report the case of a patient with concomitant chronic lymphocytic leukemia/small lymphocytic lymphoma and an embolic cerebrovascular accident related to a cardiac myxoma, who developed parenchymal central nervous system involvement of lymphoma on the ischemic bed. The patient was successfully treated with a high-dose fludarabine-based chemotherapy regimen, achieving a sustained remission. We propose that embolic breakage of the blood-brain barrier may be a major risk factor in producing central nervous system involvement. We also propose that a high-dose fludarabine-based chemotherapy regimen may be adequate to achieve a better CNS penetration and improved outcomes.